Web-Based Archiving Information System At The Ministry of Public Works and Housing Province of Jambi - Maulana, Ade Novia; Pelisa, Egidia Ratu; Afriadi, Hery (Information Technology and Science (ITScience), 2024)
This research was conducted at the Jambi Province Public Works and Public Housing Office (PUPR). This research is entitled